2023
DOI: 10.3390/polym15122627
|View full text |Cite
|
Sign up to set email alerts
|

Development of an All-Marine 3D Printed Bioactive Hydrogel Dressing for Treatment of Hard-to-Heal Wounds

Abstract: Current standard wound care involves dressings that provide moisture and protection; however, dressings providing active healing are still scarce and expensive. We aimed to develop an ecologically sustainable 3D printed bioactive hydrogel-based topical wound dressing targeting healing of hard-to-heal wounds, such as chronic or burn wounds, which are low on exudate. To this end, we developed a formulation composed of renewable marine components; purified extract from unfertilized salmon roe (heat-treated X, HTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Thus, it does not require the use of specific equipment, which is used in the method of using particular hydrogel compositions as ink for 3D photoprinting of biologically active hydrogel materials [23] and does not include the stage of post-processing of annual products [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it does not require the use of specific equipment, which is used in the method of using particular hydrogel compositions as ink for 3D photoprinting of biologically active hydrogel materials [23] and does not include the stage of post-processing of annual products [24].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown significant improvements in healing post-injury in animal models with dressings infused with different bioactive molecules, such as alginate from seaweed [79], silicate bioactive glass [80], thrombomodulin [81] and arginine derivatives [82]. With the time related information shown in lipid profiles in Figure 4, it is apparent that the phospholipids and HDL subfraction predominant lipid and lipoprotein profiles in the delayed re-epithelisation group remained constant after surgical wound debridement and became more pronounced at two weeks post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…35 To our knowledge, it is crucial to possess both contact and release antibacterial capabilities to achieve lasting and durable effects for an ideal antibacterial wound dressing. [36][37][38] Additionally, their preparation, architecture, biocompatibility, biodegradability, encapsulation property, and intelligence need to be considerations. [39][40][41] In this study, we supposed that developing a wound dressing incorporating glycyrrhizic acid (GA) and WS-CQDs could serve as an effective strategy for improving the MRSA-infected wound healing process.…”
Section: Introductionmentioning
confidence: 99%